25 Determinants of PCI success in repeat chronic total occlusion procedures following an initial failed attempt. (28th September 2016) - Ryan, N; Cuevas, C; Quiros, A; Dingli, P; Salinas, P; Vedia-Cruz, O; Nombela-Franco, L; Nuñéz-Gil, I; Jiménez-Quevedo, P; Fernandez-Ortiz, A; Gonzalo, N; Escaned, J
Abstract : Objectives: Failed percutaneous recanalisation of chronic total occlusions (CTO) constitutes a clinical conundrum. While percutaneous treatment is often abandoned in favour of medical therapy, CTO PCI expertise and alternative techniques may contribute to improve procedural success. We investigated the rates and determinants of success of repeat PCI following an initial failed attempt at recanalising the CTO percutaneously. Methods and results: Out of 445 consecutive first attempt CTO-PCI procedures in our institution, procedural failure occurred in 149 (33.5%). 64 re-PCI procedures were performed in 58 patients (39%) all had a single CTO. Procedural and outcome data in the re-PCI population was prospectively entered into the institutional database. A retrospective analysis of clinical, angiographic and procedural data was performed. Procedural success was achieved in 41 (64%) procedures. Univariate analysis of clinical and angiographic characteristics showed that re-PCI success was associated with intravascular ultrasound (IVUS) guidance (19.5% vs. 0%, p = 0.042), while failure was associated with severe calcification (30.4% vs. 9.7%, p = 0.047) and a JCTO score >3 (56.5% vs. 17.1% p = 0.003). Following multiple regression analysis the degree of lesion complexity (J-CTO score >3), IVUS use, involvement of an experienced CTO operator and LAD CTO location were significant predictors of successful re-PCI. Overall the complication rate was low, with the only MACCE two periprocedural MI's neither of which required intervention. Conclusions: Our findings suggest that re-PCI increases substantially the overall success rate of CTO revascularisation. Predictors of re-PCI success included the use of IVUS, the involvement of an experienced CTO operator in the repeat attempt and the location of the CTO.